2006
DOI: 10.4278/0890-1171-21.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Adults with Mental Retardation: Review and Research Needs

Abstract: Future research would be enhanced by including appropriately powered representative samples, by including comparison groups, by validating physical activity questionnaires, and by determining the accuracy of proxy respondents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 0 publications
1
76
1
Order By: Relevance
“…Moreover, training in motor skills enables a person to experience, explore, and understand the world around them (Reimer & Siemonsma-Boom, 2013;Schellingerhout, Smitsman, & Cox, 2005) as well as increasing selfcontrol and autonomy. However, several studies have demonstrated that people with intellectual disability have significantly fewer opportunities to experience movement and/or have lower rates of physical activity than those without disability (Draheim, Williams, & McCubbin, 2002;Emerson, 2005;Hilgenkamp, Reis, van Wijck, & Evenhuis, 2012;Lahtinen, Rintala, & Malin, 2007;Messent, Cooke, & Long, 1998;Robertson et al, 2000;Temple, Frey, & Stanish, 2006). These studies indicate that the rate of physical activity varies with the level of impairment: in general, when the intellectual disability is more severe the level of physical inactivity increases (Emerson, 2005;Peterson, Janz, & Lowe, 2008;Robertson et al, 2000).…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, training in motor skills enables a person to experience, explore, and understand the world around them (Reimer & Siemonsma-Boom, 2013;Schellingerhout, Smitsman, & Cox, 2005) as well as increasing selfcontrol and autonomy. However, several studies have demonstrated that people with intellectual disability have significantly fewer opportunities to experience movement and/or have lower rates of physical activity than those without disability (Draheim, Williams, & McCubbin, 2002;Emerson, 2005;Hilgenkamp, Reis, van Wijck, & Evenhuis, 2012;Lahtinen, Rintala, & Malin, 2007;Messent, Cooke, & Long, 1998;Robertson et al, 2000;Temple, Frey, & Stanish, 2006). These studies indicate that the rate of physical activity varies with the level of impairment: in general, when the intellectual disability is more severe the level of physical inactivity increases (Emerson, 2005;Peterson, Janz, & Lowe, 2008;Robertson et al, 2000).…”
Section: Introductionmentioning
confidence: 90%
“…Cervantes and Porretta's (2010) recent review of the literature examining PA measure ment among people with disabilities found that few studies reported validity evidence. It is questionable if previous research using self-report with assistance has captured the accurate PA behavior of adults with ID without adequate support of validity evidence (Finlay & Lyons, 2001;Fujiura & RRTC Expert Panel on Health Measurement, 2012;Temple et al, 2006). Accurate assessment of PA of people with ID is important for inclusion into larger scale epidemiological, surveillance, and intervention studies (Fujiura & RRTC Expert Panel on Health Measurement, 2012;Masse & de Niet, 2012;Matthews et al, 2011;U.S.…”
Section: Physical Activity; Self-reports; Validitymentioning
confidence: 96%
“…The most commonly reported physical activity by people with intellectual disability is walking (Stanish & Draheim, 2005;Temple, Frey, & Stanish, 2006).…”
mentioning
confidence: 99%